PENYULUHAN DAN PEMETAAN LOKASI RUMAH - Yulianto Purwono Prihatmaji (UII, 2013)
Based on observations and interviews that have been done to the villagecommunity leaders Ngaglik, obtained information that citizens still difficult to locate theother houses because the houses people from one another rather distant. With thestate of the location of the houses like this authorsplan to conduct outreach programsand mapping the location of homes that residents come to know and understand theimportance of the home location maps and know the benefits of the location map. Theirlocation map is expected to facilitate the villagers RT 02 RW 04 Ngaglik to know wherethe other houses. The event begins with identifying and observing the number ofhouseholds in the hamlet Ngaglik through the interview method to some village leaderschoosed. Implementation of counseling conducted by visiting the houses of citizens thataims to find out who the owner of the house and the location where the house will beput into a map of the location of the house the villagers choosed. The results achieved inthis program is the formation of Map Location hamlet Ngaglik RT 02 RW 04. After theimplementation of the program of Information and Mapping Location House followed bythe public, it is expected that people can know the location of other houses easily.